Demographic and Clinical Factors Associated With Verbal Memory Performance in Patients with Schizophrenia in Hospital Universiti Sains Malaysia (HUSM), Malaysia - Othman, Zahiruddin; Jamaluddin, Ruzita; Alwi, Muhammad Najib Muhammad; Ismail, Hasanah Che (ASEAN Federation of Psychiatry and Mental Health (AFPMH), 2011)
Objective: The present study aims to assess verbal memory performance in patients with schizophrenia attending HUSM and determine the relationship between the patients’ verbal memory performance and their demographic/clinical factors. Methods: A cross sectional study of 114 patients with schizophrenia attending HUSM psychiatric services from December 2007 to May 2008 was conducted. The schizophrenia symptoms as well as verbal memory performance were assessed using the Brief Psychiatric Rating Scale, the Malay version of the Calgary Depression Scale (MVCDS), and the Malay version of the Auditory Verbal Learning Test (MVAVLT). The relationship between verbal memory performance and demographic/clinical symptoms was evaluated using Pearson Correlation. Results: Overall MVAVLT scores in all the trials were lowered in patients with schizophrenia compared to average healthy controls. There were significant relationships between occupational status and MVAVLT performance in Trial A1-A5 Total; between educational level and MVAVLT performance in Trial A1 and Trial A1-A5 Total and between severities of illness and MVAVLT performance in all indexes except Trial A1 after controlled for occupation and educational level. Conclusions: Patient with schizophrenia in HUSM performed significantly worse than healthy controls in verbal memory with or without interference. There were significant relationships between MVAVLT performance and patient’s occupational status, educational level and severity of the illness but not depressive symptoms